Economics of Israel - "Horowitz, David" (Oxford, 1967)
This book contains following topics: Physical Background and Natural Resources; Basic Data; Trends and Tendencies; Output Consumption and Employment ; The Balance of payments and International Trade; Investment; Finances; The New Economic Policy in Israel.
Keywords: Economics